Strengthening Disciplinary Character Education in Elementary Students through the Implementation of Reward and Punishment - Arinal Mubarokah; Abdul Karim; Elya Umi Hanik (Universitas Sang Bumi Ruwa Jurai, 2023)
This study aims to determine the implementation of Strengthening Disciplinary Character Education to Students through the Implementation of Rewards and Punishments, and the impact of Strengthening Discipline Character Education on Students through the Implementation of Rewards and Punishments. This research uses a type of field research with a descriptive qualitative approach. Data collection techniques through observation, interviews with principals, grade 3 and 5 teachers, and students at MI NU Imaduddin Mejobo. The results showed that in its implementation, there are two types of rewards and punishments given, namely verbally and non-verbally. The impact of the implementation of rewards and punishments as a strengthening of the character of the discipline, students stick to the prevailing discipline. The discipline of Students is getting stronger, especially time discipline, learning discipline, and regulatory discipline.